The influence of silicon oxide nanoparticles on morphometric parameters of monocotyledons and dicotyledons in soil and climatic conditions of Western Siberia, as well as on microbiological soil properties - Tereshchenko, Natalya N.; Zmeeva, Olga N.; Makarov, Boris I.; Kravets, Aleksandra V.; Svetlichnyi, Valerii A.; Lapin, Ivan N.; Zotikova, Albina P.; Petrova, Lydmila V.; Yunusova, Tatyana V. (BioNanoScience)
Using a field small-plot experiment, the influence of pre-sowing seed treatment of monocotyledons and dicotyledons, namely hulless oat (Avena sativa L.) and lucerne (Medicago sativa L. subsp. varia (Martyn) Arcang.), with suspensions of silicon oxide (SiO2) nanoparticles in different concentrations on morphometric parameters and microbial cenosis of their rhizosphere was studied. It has been found that spraying of seeds with 3 × 10−5 and 3 × 10−4% suspensions of SiO2 nanoparticles accelerates the growth, and development of oat and lucerne increases the content of photosynthetic pigments in leaves and contributes to 30-40% decrease in height of an oat straw and size reduction of internodes, while increasing the specific weight of a plant by 26-38%. These findings demonstrate a higher lodging resistance of plants. In general, the monocotyledonous crop Avena sativa L. has a stronger physiological response to seed treatment with a suspension of nanoparticles than the dicotyledonous crop Medicago sativa L. The pre-sowing seed treatment of oat and lucerne induced changes in the microbial community of their rhizospheres: on the one hand, it increased proportions of nitrifying and phosphate mobilizing bacteria, as well as cellulose-decomposing actinomycetes; on the other hand, it reduced population density of microscopic fungi, while increasing a taxonomic diversity of soil fungi. In general, these findings demonstrate the improved environmental situation in rhizospheres of plants and reduced risk of root rot. © 2017, Springer Science+Business Media New York.